Kinerja Jaringan Irigasi Tingkat Tersier untuk Wilayah Pertanian Daerah Irigasi Kenconorejo UPTD-P2PU Wilayah II Subah - Dewi Bussaina Ghassani; Suwarso Suwarso (Institut Teknologi Adhi Tama Surabaya, 2021)
Irrigation is an important factor in the world of agriculture, Batang Regency is one of the regencies where the majority of the population is farmers. There are several sources or uses of water in agricultural irrigation, including by making a weir or dam. Batang Regency has several technical weirs including the Kenconorejo weir. Kenconorejo Weir Building has several complementary buildings including the weir lighthouse, weir drain door, intake gate, drainage gate and tertiary channel. The tertiary network of the Kenconorejo Irrigation Area has a total length of 8,050 m and a total agricultural area of 712 ha. With quite a long tertiary channel in the tertiary network of the Kenconorejo Irrigation Area, some of the tertiary buildings were damaged, including in the Jrakahpayung Village and Karanggeneng Villages. The results of the calculation of the discharge of tertiary channels in Kenconorejo are obtained, Jrakahpayung Village 36 l/sec with a land area of 18 ha, Kedungsegog 320 l/sec with a land area of 210 ha, Kenconorejo1 212 l / sec with an area of 150 ha, Kenconorejo2 260 l/sec with an area of 148 ha, Ponowareng Village 185 l / sec with an area of 120 ha, and the last is Karanggeneng Village with a total discharge of 94 l / sec and an area of 66 ha. And with the existence of several damaged small complementary buildings, this is of course homework for the PSDA Office which has the authority to manage irrigation systems in a government agency.